Modern problems of bronchial tuberculosis in the world and the Russian Federation: A review - Nikita V. Chumovatov; Ekaterina G. Polushkina; Natalya A. Chernykh; Oksana G. Komissarova (Consilium Medicum)
In the Russian Federation there is a positive trend in reducing the incidence of tuberculosis. However, there is a tendency to increase the prevalence of tuberculosis in the bronchi. According to foreign authors, the prevalence of bronchial tuberculosis ranges from 10% to 40%. There are no official statistics on the incidence of bronchial tuberculosis in the Russian Federation. The main contingent of bronchial tuberculosis lesions are young non-smoking women. At the same time, the most common target is the left main bronchus. Currently, no additional methods have been developed in the scheme of specific treatment of patients with pulmonary tuberculosis complicated by bronchial tuberculosis. It is important to understand that the eradication of MBT after an effective course of chemotherapy does not prevent the formation of cicatricial bronchial stenosis. It is also important to note that bacterial excretion in patients with bronchial tuberculosis is much more common than in patients with a comparable process in the lungs, but without bronchial damage. Consequently, tuberculosis of the trachea and bronchi has not only clinical, but also great epidemiological significance.